Analisis Pengaruh Kecepatan Tripping terhadap Respons Tekanan Swab dan Surge pada Sumur Deviasi Tinggi Emn Lapangan N - Muhammad Sulaiman; Ali Wardhana Putra (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Tripping pipe operations in highly deviated wells can generate dynamic pressure variations in the form of surge pressure and swab pressure, which may affect wellbore pressure stability. This study aims to analyze the effect of tripping speed variations on transient pressure response in Well EMN, Field N, using Transient Hydraulics simulations performed with Landmark WellPlan software. Simulations were conducted under closed pipe conditions with tripping speeds of 60, 90, and 120 ft/min using a Water-Based Mud (WBM) system containing Xanthan Gum and modeled with the Bingham Plastic rheological approach. The simulation results indicate that increasing tripping speed leads to higher transient pressure amplitudes, with a maximum surge pressure spike of 10.15 ppg at 120 ft/min and a minimum swab pressure of 9.33 ppg. All pressure responses remained within the operating window defined by a pore pressure of 8.33 ppg and a fracture gradient of 14.32 ppg. A tripping speed of 60 ft/min is recommended as the most conservative operating condition to minimize pressure fluctuations during tripping operations.